Sutureless vs. rapid-deployment valve: a systemic review and meta-analysis for a direct comparison of intraoperative performance and clinical outcomes - Wang, Chenhao; Xie, Yi; Zhang, Hongwei; Yang, Peng; Zhang, Yu; Lu, Chen; Liu, Yu; Wang, Haiyue; Xu, Zhenyuan; Hu, Jia (Frontiers in Cardiovascular Medicine, 2023)
Background Sutureless and rapid-deployment valves are bioprostheses anchoring within the aortic annulus with few sutures, and they act as a hybrid of conventional surgical and transcatheter valves under aortic valve replacement. Considering that the 3F Enable valve is now off-market, the only two sutureless and rapid-deployment valves available on the world marketplace are the Perceval and Intuity valves. However, a direct comparison of the function of these two valves eludes researchers. Purpose Against this background, we performed this systematic review and meta-analysis comparing the intraoperative performance and early clinical outcomes between the Perceval valve and the Intuity valve under sutureless and rapid-deployment aortic valve replacement. Methods We systematically searched electronic databases through PubMed/MEDLINE, OvidWeb, Web of Science, and Cochrane Central Register of Controlled Trials (from the establishment of the database to November 17, 2022, without language restriction) for studies comparing the sutureless valve (the Perceval) and the rapid-deployment valve (the Intuity) under aortic valve replacement. Our primary outcomes were early mortality and postoperative transvalvular pressure gradients. The secondary outcomes were defined to include aortic cross-clamp and cardiopulmonary bypass time, paravalvular leak (any paravalvular leak, moderate-to-severe paravalvular leak) after aortic valve replacement, need for pacemaker implantation, postoperative neurological events (stroke), and intensive care unit stay. Results This meta-analysis included ten non-randomized trials with 3,526 patients enrolled (sutureless group = 1,772 and rapid-deployment group = 1,754). Quality assessments were performed, with the mean scores of the studies reading 6.90 (SD = 0.99) out of 9 according to the Newcastle–Ottawa Scale. Compared with rapid-deployment aortic valve replacement, sutureless aortic valve replacement was associated with higher mean and peak transvalvular pressure gradients postoperatively. In contrast, aortic cross-clamp and cardiopulmonary time were needed less in sutureless aortic valve replacement vs. rapid-deployment aortic valve replacement. There was no evidence of significant publication bias observed by the funnel plot and Egger's test. Conclusions For postoperative hemodynamics, sutureless aortic valve replacement was associated with increased mean and peak transvalvular pressure gradients compared with rapid-deployment aortic valve replacement. In sharp contrast, sutureless aortic valve replacement significantly reduced the amount of time needed for fixing the aortic cross-clamp and the cardiopulmonary bypass procedure. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022343884.